Active ageing policies and delaying retirement: comparing work-retirement transitions in Austria and Germany. Issue 2 (4th July 2021) - Schmidthuber, Lisa; Fechter, Charlotte; Schröder, Heike; Hess, Moritz
Abstract: We investigate how labour market and pension measures associated with active ageing influence retirement behaviour in Austria and Germany. We focus on two conservative welfare states and evaluate how individuals respond to comparable pension scheme changes. Using the Survey of Health, Ageing and Retirement in Europe, findings point to increasing average actual retirement ages in both countries. Early retirement becomes less important while working until pension age has gained in significance. In particular, findings point towards greater de-standardisation of retirement transitions, though to a different extent across the two countries. Whereas gender differences are still prevalent in Austria, in line with traditional conservative welfare state characteristics, we find that Germany exhibits lower gender differences, but instead displays stronger inequalities between education groups. We argue that social risks emerge in Germany that are usually found in liberal welfare states. We suggest that this trend is reinforced by retirement policies that focus on "pushing" individuals out of employment. This study contributes to the understanding of how individuals respond to national policy incentives when making retirement transitions.